Necro-hemorrhagic enteritis and necrotizing hepatitis in green anaconda (Eunectes marinus) - Souza, Bruno Camilo de; Cavasani, João Paulo da Silva; Silva, Wuglenya Daislla Martins da; Pescador, Caroline Argenta; Colodel, Edson Moleta; Furlan, Fernando Henrique (Brazilian Journal of Veterinary Pathology, 2025)
An adult, male, green anaconda (Eunectes marinus) from “Universidade Federal de Mato Grosso” (UFMT) Zoo’s collection showed apathy, anorexia and bloody feces. This snake died during clinical evaluation and was necropsied.